Advancing Justice Through Our Students. (7th June 2017) - Applegate, Brandon K.
Abstract : One avenue by which criminal justice scholars can advance the discipline is through preparing students to enter the field. Popular commentary and some international analyses suggest that recent college graduates lack in employability skills, and they secure adequate employment at a disappointing rate. When the field of focus is narrowed to criminal justice, however, the picture is less worrisome. Although the data show that our students lag in securing employment in positions that require a bachelor's degree, our students feel prepared for work, find employment after graduating, and tend to improve their situation when pre-graduation and post-graduation employment are compared. Even so, I encourage justicians to take deliberate actions that will help launch the next generation of professionals into successful careers and lead to positive contributions to the future of criminal justice.